Long term sea level rise trend in Malaysia using tide gauges [electronic resource] - Abdul Hadi Kamaruddin 1992- 632356 (2016)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2016